METHODOLOGY OF TEACHING PSYCHOLINGUISTICS IN THE FIELD OF JOURNALISM. PSYCHOLINGUISTIC ASPECTS IN TEACHING ENGLISH IN JOURNALISM - Begibaeva Farogat Bakhtiyor kizi (Western European Studies, 2024)
The article deals with the relevance and necessity of teaching psycholinguistics in the sphere of journalism. The main methodological approaches to teaching psycholinguistic disciplines are analyzed, taking into account the specifics of journalistic activity. Innovative methods and forms of teaching are proposed, which contribute to the development of future journalists' skills in analyzing and interpreting speech, as well as creating effective and persuasive texts
Keywords: psycholinguistics; journalism; teaching methodology; language competence